Escalating Hydrological Extremes and Whiplashes in the Western U.S.: Challenges for Water Management and Frontline Communities - Wenzhao Li; Surendra Maharjan; Joshua B. Fisher; Thomas Piechota; Hesham El‐Askary (Earth's Future)
Abstract The Western U.S. is experiencing significant changes in its hydrological dynamics, marked by increased variability and rapid “whiplash” shifts between extreme drought and flood conditions. This study quantified these changes using a customized hydrological water year index, which correlated better with surface water storage in the basins than other drought/wetness indicators. Application of the index revealed heightened hydrological extremes and whiplash events post‐2015 in all Western U.S. basins, with nearly 72% of stations facing critically dry conditions in 2021 and over 54% experiencing extreme wet conditions in 2023. Future projections indicate a decline of 8.5%–13.2% in non‐extreme water year types across major basins, accompanied by increases in both extreme wet and dry water year types. Our findings suggest that similar levels of multi‐year drought duration and water deficits will likely occur regardless of future warming scenarios. This trend significantly impacts agriculture, the environment, and urban water use sectors. Notably, vulnerable frontline communities with higher risks and lower resilience experience disproportionate impacts from droughts compared to other communities.